Story telling as a pedagogical resource in portuguese language classes in the early years of elementary school (Research, Society and Development, 2022)
The article expresses the perception of Storytelling as a Pedagogical Resource in Portuguese Language Classes in the Initial Years of Elementary School. Aiming to emphasize the importance of storytelling for socio-cognitive development in the literacy cycle. Thus, the study sought to contextualize alternatives to facilitate student learning during teaching-learning and maximize satisfactory results on the subject under discussion, having as a problem: What is the contribution of storytelling to the development of student learning in teaching fundamental? How can this process benefit student learning and what is its relevance to self-development in the learning process in Elementary School? In the search for an answer to this question, a bibliographic review was used, which presented data in a qualitative way, with an emphasis on national and international credibility. The study is justified by the fact that storytelling allows the student to acquire numerous skills and competences that provide the enrichment of learning. Thus, it is essential for the development of the student, and, therefore, it is necessary to use this practice as a way of improving the quality of teaching and learning, in terms of literacy, because the contact with the narrated story makes students feel stimulated to read, write and interpret, being essential factors for the integral formation of the individual.